The Influence of Discharge Planning on Family Preparedness in Caring for Elderly Stroke Patients: A Systematic Review - Mardhatillah Mardhatillah; Etty Rekawati; Kuntarti Kuntarti (GLOBAL HEALTH SCIENCE GROUP, 2025)
Stroke is the second leading cause of death and the third leading cause of disability worldwide . Lack of understanding and information received by families, as well as minimal involvement during patient care, can lead to unpreparedness in caring for patients. Discharge planning is an important process in ensuring a safe transition of care from hospital to home, especially for elderly stroke patients. Family readiness to care for elderly stroke at home is greatly influenced by the effectiveness of discharge planning . Objective: This study aims to examine and analyze the effect of discharge planning on family readiness to care for elderly stroke. Method: Five databases through article searches adjusted to the PICO question formulation consisting of ScienceDirect, ProQuest, Googlescholer, Sage Journals, and Taylor and Franchise from 2019-2024. The keywords used are Stroke in Elderly, older, Older adult, Cerebral Infarction AND Discharge Planning AND family readiness, , family satisfaction.The number of articles found was 1,335, and after screening, 5 articles were analyzed. Results: There were five selected articles. Based on the results of the analysis, comprehensive discharge planning, involving education, training, and psychosocial support, has been shown to increase family readiness to care for elderly stroke at home. With a Randomized Controlled Trial (RCT ) and quasi-experimental design . Conclusion: Effective discharge planning can increase family readiness and satisfaction in caring for elderly stroke at home.